The impact of intellectual capital disclosure in supporting theorganizational performance - عبد الكريم جاسم أحمد; صباح شعير حاضر; فخري محمد محمد (Finance and Business Economies Review, 2019)
Intellectual Capital has become one of important tools to achieve organizations success in the business world. Therefore, it is important to consider the intellectual capital in order to determine the economic value of any organizations. The disclosure of intellectual property and its basic components is essential to show the Organization independency as it has direct impact on its performance. This objective if the study is to measure the impact of the disclosure of intellectual capital and subsequently on the organizational performance in selected Iraqi organizations. The study has hypothesized that there is a direct impact the disclosure of intellectual capital on the organizations performance in selected organizations of Iraq. The study has employed the descriptive approach and secondary source of data from previous studies and primary source of date through the questionnaire based survey, which formed the conceptual framework of the study. The results of the study showed that there is negative impact of the on the intellectual capital if the organization has not adapted the disclosure.